Sociology today social transformations in a globalizing world - Sales, Arnaud; Sage eBooks; International Sociological Association (Los Angeles : SAGE, 2012)
This collection effectively mirrors the diversity and variety of transformations underway in today's societies and transnational spaces. It offers a cutting edge understanding of what is happening in our life worlds, work lives and frames of social existence.
Published in association with the International Sociological Association.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social change; Sociology; Electronic books